How Sanctions Work
XV, 292 p.
Keywords: How Sanctions Work surveys theories of international sanctions and offers detailed analyses of the effect of sanctions on apartheid South Africa. Chapters by respected international experts cover cultural isolation, oil and military embargoes, trade boycotts, financial sanctions and divestment, consequences for black South Africans, and regional effects. The book shows how sanctions both directly and indirectly hurt the apartheid regime while in some cases offering succour to the anti-apartheid movement.